2014
DOI: 10.1186/cc13902
|View full text |Cite
|
Sign up to set email alerts
|

The role of CXCL10 in the pathogenesis of experimental septic shock

Abstract: IntroductionThe chemokine CXCL10 is produced during infection and inflammation to activate the chemokine receptor CXCR3, an important regulator of lymphocyte trafficking and activation. The goal of this study was to assess the contributions of CXCL10 to the pathogenesis of experimental septic shock in mice.MethodsSeptic shock was induced by cecal ligation and puncture (CLP) in mice resuscitated with lactated Ringer’s solution and, in some cases, the broad spectrum antibiotic Primaxin. Studies were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
(82 reference statements)
2
27
0
Order By: Relevance
“…However, as shown in previous studies from our lab and others, NK cells participate in the propagation of acute inflammation and physiological dysfunctions in experimental models of polymicrobial peritonitis (31), endotoxin shock (32), pneumococcal pneumonia (33), systemic Escherichia coli and Streptococcus pyogenes infection (34, 35), and polytrauma (36). Our lab previously showed that NK cells quickly migrate to sites of infection during intraabdominal sepsis, in a manner regulated by the chemokines CXCL9 and CXCL10 (23, 3739). During sepsis, activated NK cells increased production of IFN-γ, which is known to potentiate inflammation by activating macrophages, dendritic cells and other innate immune cells (31, 40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown in previous studies from our lab and others, NK cells participate in the propagation of acute inflammation and physiological dysfunctions in experimental models of polymicrobial peritonitis (31), endotoxin shock (32), pneumococcal pneumonia (33), systemic Escherichia coli and Streptococcus pyogenes infection (34, 35), and polytrauma (36). Our lab previously showed that NK cells quickly migrate to sites of infection during intraabdominal sepsis, in a manner regulated by the chemokines CXCL9 and CXCL10 (23, 3739). During sepsis, activated NK cells increased production of IFN-γ, which is known to potentiate inflammation by activating macrophages, dendritic cells and other innate immune cells (31, 40).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was described previously (23). In brief, mice were anesthetized with 2% isoflurane in oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Natural killer cells rapidly migrate to sites of bacterial infection. CXCR3‐expressing NK cells quickly migrate from secondary lymphoid organs to the peritoneal cavity within 4–6 hr after the initiation of intra‐abdominal sepsis, in a manner regulated by the chemokines CXCL9 and CXCL10 . CXCR3 + NK cells are the murine equivalent of human CD56 bright NK cells, both of which produce significantly more IFN‐ γ than CXCR3 − CD56 dim NK cells .…”
Section: Nk Cells: Friend or Foe During Sepsis?mentioning
confidence: 99%
“…CXCR3-expressing NK cells quickly migrate from secondary lymphoid organs to the peritoneal cavity within 4-6 hr after the initiation of intra-abdominal sepsis, in a manner regulated by the chemokines CXCL9 and CXCL10. 90,91 CXCR3 + NK cells are the murine equivalent of human CD56 bright NK cells, both of which produce significantly more IFN-c than CXCR3 À CD56 dim NK cells. 92 Our laboratory subsequently performed phenotypic characterization of these CXCR3 + mouse NK cells in the context of sepsis.…”
Section: Detrimental Role Of Nk Cells During Experimental Sepsismentioning
confidence: 99%
“…Interferon (IFN)-γ-induced protein 10 (IP-10/CXCL10) appears to contribute to the pathogenesis of several diseases and has been suggested as a potential biomarker of viral infection1011, late-onset bacterial infection in premature infants12, and a promising biomarker of sepsis and septic shock1314. Combined analysis of IP-10 and IFN-γ has also been reported as a useful biomarker for diagnosis and monitoring therapeutic efficacy in patients with active tuberculosis151617, and both remain detectable in the urine of patients with pulmonary diseases in the absence of renal dysfunction18.…”
mentioning
confidence: 99%